Association of Meal and Snack Patterns With Mortality of All‐Cause, Cardiovascular Disease, and Cancer: The US National Health and Nutrition Examination Survey, 2003 to 2014 - Wei Wei; Wenbo Jiang; Jiaxin Huang; Jiaxu Xu; Xuanyang Wang; Xitao Jiang; Yu Wang; Guili Li; Changhao Sun; Ying Li; Tianshu Han (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Although accumulating evidence has demonstrated that consumption time of energy and macronutrients plays an important role in maintaining health, the association between consumption time of different foods and cardiovascular disease, cancer, and all‐cause mortalities is still largely unknown. Methods and Results A noninstitutionalized household population of the US 21 503 participants from National Health and Nutrition Examination Survey was included. Meal patterns and snack patterns throughout a whole day were measured using 24‐hour dietary recall. Principal component analysis was performed to establish dietary patterns. Cox proportional hazards models were used to evaluate the association between dietary patterns across meals and cardiovascular disease (CVD), cancer, and all‐cause mortalities. During the 149 875 person‐years of follow‐up, 2192 deaths including 676 deaths because of CVD and 476 because of cancer were documented. After adjusting for potential confounders, participants consuming fruit‐lunch had lower mortality risks of all‐cause (hazard ratio [HR], 0.82; 95% CI, 0.72–0.92) and CVD (HR, 0.66; 95% CI, 0.49–0.87); whereas participants who consumed Western‐lunch were more likely to die because of CVD (HR, 1.44; 95% CI, 1.10–1.89). Participants who consumed vegetable‐dinner had lower mortality risks of all‐cause, CVD, and cancer (HRall‐cause, 0.69; 95% CI, 0.60–0.78; HRCVD, 0.77; 95% CI, 0.61–0.95; HRcancer, 0.63; 95% CI, 0.48–0.83). For the snack patterns, participants who consumed fruit‐snack after breakfast had lower mortality risks of all‐cause and cancer (HRall‐cause, 0.78; 95% CI, 0.66–0.93; HRcancer, 0.55; 95% CI, 0.39–0.78), and participants who consumed dairy‐snack after dinner had lower risks of all‐cause and CVD mortalities (HRall‐cause, 0.82; 95% CI, 0.72–0.94; HRCVD, 0.67; 95% CI, 0.52–0.87). Participants who consumed a starchy‐snack after main meals had greater mortality risks of all‐cause (HRafter‐breakfast, 1.50; 95% CI, 1.24–1.82; HRafter‐lunch, 1.52; 95% CI, 1.27–1.81; HRafter‐dinner, 1.50; 95% CI, 1.25–1.80) and CVD (HRafter‐breakfast, 1.55; 95% CI, 1.08–2.24; HRafter‐lunch, 1.44; 95% CI, 1.03–2.02; HRafter‐dinner, 1.57; 95% CI, 1.10–2.23). Conclusions Fruit‐snack after breakfast, fruit‐lunch, vegetable‐dinner, and dairy‐snack after dinner was associated with lower mortality risks of CVD, cancer, and all‐cause; whereas Western‐lunch and starchy‐snack after main meals had greater CVD and all‐cause mortalities.